Efecto del uso de la gonadotropina coriónica equina sobre la calidad extrínseca e intrínseca del huevo de codorniz - Mendoza Escobar, Keyla Roxana (2025)
This research was carried out with the aim of evaluating the effect of the hormone equine chorionic gonadotropin on the extrinsic and intrinsic quality of quail eggs. This research was carried out at the Faculty of Agricultural Sciences, in the Veterinary Medicine Career within the Seedbed Project "Evaluation of the Productive Characteristics of Quail (Coturnix coturnix) in the Tropics", with the following objectives: Identify the extrinsic quality of the quail egg through the variation characteristics; weight, shell thickness, color and shape index and Determine the intrinsic quality of the quail egg through the analysis of yolk index, albumen index, yolk color, Haugh Units. In which the experimental units will be distributed with a completely random design with three treatments versus a control, with two repetitions, giving a total of eight experimental units which will be made up of 12 animal units, with a total of 96 animals in the experiment, where the treatment with the highest egg weight was T2 with 12.22 g compared to T3 with 11.58 g, T0 with 11.50 g and T1 with 11.43 g. The treatment with the best shell thickness was T3 with 0.22 mm compared to T1 with 0.21 mm, T0 with 0.19 mm and T2 with 0.18 mm. The most common egg color was T1, representing a mottled light brown, demonstrating that this hormone had no significant effect on the quail egg. Regarding egg morphology, the best treatment was T0, with 80.75%, compared to T3 with 80.19%, T2 with 80.17% and T1 with 78.34%. On the other hand, within the intrinsic characteristics of the quail egg, the treatment that obtained the highest yolk index was T2 with 32.55 mm, compared to T3 with 32.03 mm, T1 with 28.20 and T0 with 27.79. In the albumen index, treatment T2 with 8.81 mm was the one that obtained the highest index in the white, compared to the other treatments T1 with 8.32 mm, T0 with 7.74 mm, T3 with 7.55 mm. Regarding the yolk color, the treatment that obtained the best color was T3 with 5.15, followed by T2 with 4.72, T1 with 4.57 and T0 with 4.43. In Hugh Units, treatment T2 with 89.87% was the highest percentage, compared to treatments T0 with 89.17%, T1 with 88.96% and T3 with 88.91%. Keywords: quail, hormone, gonadotropin, extrinsic, intrinsi